La rivalité SNCF/DB, une tentative d’interprétation géostratégique à l’échelle ouest-européenne - Antoine BEYER (L'Espace Politique)
Although mentioned in the Treaty of Rome (1957), the European Transport Policy only came to life much later, as a result of demands by the European Parliament and in the context of the Single European Act (1986). This policy gradually took on a strong liberal dimension. During the 1990s, several European packages were introduced into national legal systems that tried to end the spatial monopolies within each state's control. In this perspective rail seems to be a latecomer compared with the other transport modes. After decades of institutional stability, railway companies have had to adapt their strategies to a new European context. The present paper tries to demonstrate how a national context deeply embedded in history and national geography continues to dictate priorities. A geopolitical reading of a liberalized rail transport suggests the unlikelihood of any simple, footloose industry prevailing within the single European market, without any reference to former national identities. On the contrary, vanishing national borders introduce new challenges and insecurity for the rail companies, which have to be interpreted in a territorial dimension.